Respuesta :

Answer:x=e

Step-by-step explanation:

To solve the equation

ln

(

)

+

ln

(

2

)

=

3

ln(x)+ln(x

2

)=3, you can simplify it first by combining the logarithms:

ln

(

)

+

ln

(

2

)

=

ln

(

2

)

=

ln

(

3

)

ln(x)+ln(x

2

)=ln(x⋅x

2

)=ln(x

3

)

So, the equation becomes:

ln

(

3

)

=

3

ln(x

3

)=3

Now, to eliminate the natural logarithm, you can rewrite the equation in exponential form:

ln

(

3

)

=

3

e

ln(x

3

)

=e

3

3

=

3

x

3

=e

3

Now, solve for

x:

=

3

3

x=

3

 

e

3

=

x=e